Professional self-concept and its relationship to self-sufficiency Nada Educational guides (Journal of the College of Basic Education, 2022)
The professional self-concept has two dimensions: the first is positive and raises the level of the profession, while theEducational counselors who hold a negative self-concept about the counseling profession are a problem in the processeducators and could not perform their duties to the fullest, but rather did not contribute to solving problems in a waypositive and complementary; The professional self-concept of educational counselors has a great and important role in achieving thisThe work entrusted to him and the problems he solves, and assisting those who are guided in finding appropriate solutionsFor it, the successful mentor must be characterized and endowed with personal, physical, mental and social-cultural qualities